Rare bird documentation form for Northern Goshawk at Lincoln Township in Story County in 1983 - LaGrange, Tedet al (1983)
Rare bird documentation form for a Northern Goshawk at Lincoln Township in Story County, IA on March 15, 1983. Epson - sheet feed